Ուաուշի ճակատամարտը (պատմա–համեմատական վերլուծություն) - Գրեկյան, Երվանդ («Զանգակ - 97»)
One of the most famous events from the history of the Ancient Near East was the "Eight Year's Campaign" of Saigon II of Assyria to Uraitu (c. 714 В. C.). It was the culmination of confrontation between thesc powerful empires. The key battle took place on Mt. Uaush (modern Sahand). The paper deals with the Battie based on analysis of the text "Letter to Assur" - an Assyrian cuneiform source and concludes а new possible reconstruction of it The author puts down a hypothesis, according to which no oncoming battle took place on Mt. Uaush -as was suggested by the scholars to this date. He thinks that Sargon's victory was achieved by an unexpectcd attack of Assyrian elite group of troops led personally by the king on headquarters of Rusa - king of Uraitu and his cavalry units, which led up to losing of connections between the headquarters and the army units. It also made psychological effect: the soldiers were demoralized, the troops have come asunder, they didn't try to defend and escaped. The Urartian army was fkted to suffer a terrible defeat.
Keywords: Պատմություն